Managing Skin Ageing as a Modifiable Disorder—The Clinical Application of Nourella® Dual Approach Comprising a Nano-Encapsulated Retinoid, Retilex-A® and a Skin Proteoglycan Replacement Therapy, Vercilex® - Jan Wadstein; Israel Sánchez Alvarez; Lidia Bernal López (Cosmetics, 2022)
Skin ageing is a progressive, but modifiable, multi-factorial disorder that involves all the skin’s tissues. Due to its wide range of physiological and psychosocial complications, skin ageing requires rigorous clinical attention. In this review, we aim to encourage clinicians to consider skin ageing as a disorder and suggest a novel, dual approach to its clinical treatment. Topical retinoids and per-oral proteoglycans are promising, non-invasive, therapeutic modalities. To overcome the low bioavailability of conventional free retinoids, Nourella® cream with Retilex-A® (Pharma Medico, Aarhus, Denmark) was developed using a proprietary nano-encapsulation technology. The nano-encapsulation is a sophisticated ‘permeation/penetration enhancer’ that optimises topical drug delivery by increasing the surface availability and net absorption ratio. Treatment adherence is also improved by minimising skin irritation. Interventional evidence suggests the greater efficacy of Retilex-A® in improving skin thickness and elasticity compared with conventional free forms. It is also reported that the rejuvenating efficacy of Retilex-A® and tretinoin are comparable. Another skin anti-ageing approach is proteoglycan replacement therapy (PRT) with Vercilex®. Vercilex® in Nourella® tablet form has the potential to ameliorate proteoglycan dysmetabolism in aged skin by activating skin cells and improving collagen/elastin turnover. Replicated clinical trials evidenced that PRT can significantly enhance the density, elasticity and thickness of both intrinsically aged and photoaged skin. Evidently, Vercilex® and Retilex-A® share a range of bioactivities that underlie their synergistic activity, as observed in a clinical trial. Dual therapy with Nourella® tablets and cream produced greater effects on skin characteristics than monotherapy with each of the two treatments. In conclusion, Nourella® cream and tablets are safe and effective treatments for skin ageing; however, combining the two in a ‘dual skin rejuvenation system’ significantly improves treatment outcomes.